Objetos turbulentos, territórios instáveis: uma história das representações dos aparelhos elétricos no espaço doméstico (1940-60) - Arruda, Márcia Bomfim de (2010)
The title of this thesis is Turbulant Objects, unstable territories. A history of the representations of home electric appliances in the domestic household (1940-60). It deals with home automation spanning mainly the post Second World War period, when electric home appliances become accessible to the middle class in the states of Rio de Janeiro and of São Paulo. It is a study in Cultural History concerning the representation of electric appliances appearing mainly in adds and as articles in magazines such as Casa e Jardim and O Cruzeiro . The representations arose from the thoughts which reflect a means of trying to conform objects, as well as the whole household and its routines to a certain scientific rationality. Such rationality is based on the knowledge of different specialities as architecture, engineering and design. Electric appliances became a spectacle for the consumer society and which values more and more the appearance of things. In the domestic field a technological aesthetics constitutes itself during this period, characterized by furniture, equipments and appliances manufactured with new materials, as well as architecture. Through automation, the means of doing domestic work changed and the idea of producing more in less time a rule in the work industry is extended to the household